The responsibilisation of learners in the Australian Foundation Skills apparatus: making up motivated, choice-making customers. Issue 1 (2nd January 2022) - Argent, Garry; Brown, Seth; Kelly, Peter
ABSTRACT: This paper contributes to debates that shaped a special issue of Discourse in 2017 by taking the debate about responsibilisation in education into the realm of Foundations Skills in Australia. The difficulties that many Australian adults experience with low levels of language, literacy and numeracy skills (Foundation Skills), have been widely identified. It has been claimed that almost half of Australia's working age population have Foundation Skills at levels that do not allow them to meet the complex demands of work and life. The paper describes the Foundation Skills policy apparatus that has developed in Australia, and discusses how the sector is characterised by aspects of marketisation and commodification. We argue that the Foundation Skills learner is imagined as an individual, choice making, responsible consumer and increasingly made responsible for carrying the burden of the development of their 'human capital' so that they can secure a less parlous participation in precarious labour markets.